METROLOGICAL MODELING OF DIMENSIONAL OPERATIONAL INSPECTION PROCESSES AS AN INSTRUMENT OF RELIABILITY ASSURANCE - D. V. Solomakho (Приборы и методы измерений)
The article describes issues of operational inspection reliability assurance. Reliability is the mast important property of inspection. Reliability is defined as the probability of correct decision making during the inspection. This probability depends on the measurement error and tolerance range ratio, position of acceptance limits and technological process stability. Existing approaches to measurement tolerance design, which are also used in ГОСТ 8.051 and РД 50-98-86, do not take into consideration the influence of technological process stability on inspection reliability. Thus, these approaches are to be reconsidered.